Late Iron Age and Roman settlement at Bozeat Quarry, Northamptonshire excavations 1995-2016 - Atkins, Rob 1968- (Archaeopress Archaeology, 2018)
MOLA (formerly Northamptonshire Archaeology), has undertaken intermittent archaeological work within Bozeat Quarry over a 20-year period from 1995-2016 covering an area of 59ha. This volume presents their findings
Keywords: Vor- und Frühgeschichte; Excavations (Archaeology) / England / Bozeat; Iron age / England / Bozeat; Ausgrabung; Funde; Bozeat (England) / Antiquities; Bozeat (England) / Antiquities, Roman; Great Britain / History / Roman period, 55 B.C.-449 A.D.; Bozeat